Isolation and pathogenicity of a variant porcine epidemic diarrhea virus field strain with high adaptability to Vero cell - Liao, Tianjing; Zhang, Yi; Ma, Huanhuan; Wang, Zhanchang; Zhou, Ao; Zhang, Yu; Zhang, Zhengfan; Guo, Shuangshuang; Hou, Yongqing; Li, Zhonghua; Wu, Tao (Frontiers in Veterinary Science, 2025)
Since 2010, new outbreaks of porcine epidemic diarrhea (PED) caused by porcine epidemic diarrhea virus (PEDV) variant strains have brought significant economic losses to world pig industry. In this study, we isolated a PEDV strain from a new PED outbreak farm in 2024. The strain was identified through RT-PCR, indirect immunofluorescence assay and purified through plaque assay. This virus showed high adaptability to Vero cell during the process of passage and named as HB-2024. Phylogenetic analysis of the S gene showed that the HB-2024 strain was clustered into G2b subgroup. Amino sequence analysis showed that the S protein of the HB-2024 strain had a unique character beside the N terminal of the fusion peptide, which might lead to its high adaptability to Vero cell. We also performed a piglet infection experiment to test its pathogenicity. All piglets infected with this virus showed obvious diarrhea and their small intestines showed serious pathological damage. These results suggest that the HB-2024 strain is a G2b subtype variant that adapts well to Vero cell and can be used to study the adaptive mechanisms of PEDV.